Correction of Orbital Deformity in Camurati-Engelmann Disease with PEEK Lateral Wall Implants. (22nd April 2021) - Howe, Thomas E.; Goonesekera, Damithri T.; Lee, Nicolas J.; Salvi, Sachin M.
Camurati-Engelmann Disease is a rare congenital sclerosing bone dysplasia condition. Affected patients manifest bony abnormalities including thickening of the skull base and orbital bones. The resulting orbital volume reduction associated with this condition can cause exophthalmos, distorting the facial profile. The authors report a 33-year-old man with a diagnosis of Camurati-Engelmann Disease exhibiting exophthalmos who was successfully treated with the insertion of bilateral lateral orbital wall patient specific PEEK implants via a bi-coronal flap approach. This case highlights the novel application of modern cutting-edge technology in the treatment of proptosis in Camurati-Engelmann Disease.